A Decision for Life – Treatment decisions in newly diagnosed families with spinal muscular atrophy (SMA). (January 2021) - Gusset, Nicole; Erbas, Yasemin; Germanenko, Olga; Rucinski, Kacper; Stumpe, Eva; de Lemus, Mencía
Highlights: With several treatments available, families with a child with SMA are faced with challenging decisions. In order to make informed decisions, families need to understand the full picture of the disease, including the patient perspective on quality of life. A transparent discussion about the range of potential outcomes of different treatments, followed by shared decision-making is essential. Predictive factors for treatment outcomes remain unclear, therefore potential treatment benefit must be assessed on an individual level.